The Influence of Implementing the Project to Strengthen the Pancasila Learning Profile on the Formation of Students' Civic Disposition - Jamilah, Jamilah; bin Abd Rahim, Norani; Juliansyah, Barkah; Melati, Prima (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The increasing number of juvenile delinquency cases involving students is very disappointing. Similarly, the low level of morality found by researchers at the research location became the basis for conducting this research. The purpose of this research is to describe the implementation of the Pancasila Student Profile Strengthening Project in shaping citizenship dispositions, describe the formation of citizenship dispositions through this project, and determine the extent of its influence on students' citizenship dispositions. Methods: The research approach used is a quantitative approach with descriptive methods. The data used include primary and secondary data, which were collected through observation, questionnaire distribution, and documentation. This research was conducted at SMPN 1 Kadungora, with a population of all eighth grade students from grades A to I, and a sample of 66 respondents. Results: The results of the study indicate that the implementation of the Pancasila Student Profile Strengthening Project has an effect on the formation of students' citizenship dispositions. This is evidenced by the development of behavioral habits among students that reflect citizenship dispositions, such as respecting the customs of others, complying with school and community norms and rules, upholding the value of tolerance, and having the courage to express opinions. Novelty: This study focuses on the application of the noble values ​​of Pancasila, presented in the form of projects in classroom learning. It is also implemented in extracurricular activities to strengthen the profile of Pancasila-abiding students.